2007
DOI: 10.1038/sj.npp.1301335
|View full text |Cite|
|
Sign up to set email alerts
|

Gender-Dependent Association of the Functional Catechol-O-Methyltransferase Val158Met Genotype with Sensation Seeking Personality Trait

Abstract: The gene encoding cathechol-O-methyltransferase (COMT) contains a common functional missense polymorphism (Val158Met) that regulates dopamine in an allele-dependent manner. A pivotal role of dopamine neurotransmission in the prefrontal cortex has been implicated in drug-seeking behavior and related personality traits, such as sensation seeking, with some evidence for a gender-specific association. Here, we tested the hypothesis that the COMT Val158Met polymorphism modulates the personality dimension, sensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 43 publications
6
63
1
1
Order By: Relevance
“…A sex-by-genotype interaction (po0.0005) was seen by Lang et al (2007) who showed that the Val 158 allele was associated with the personality trait of sensation-seeking in women. This finding is the latest in a line of studies that show relationships between COMT genotype and personality traits in women but not in men.…”
Section: Sexually Dimorphic Effects Of Comt Genotype On Psychiatric Dmentioning
confidence: 91%
See 1 more Smart Citation
“…A sex-by-genotype interaction (po0.0005) was seen by Lang et al (2007) who showed that the Val 158 allele was associated with the personality trait of sensation-seeking in women. This finding is the latest in a line of studies that show relationships between COMT genotype and personality traits in women but not in men.…”
Section: Sexually Dimorphic Effects Of Comt Genotype On Psychiatric Dmentioning
confidence: 91%
“…The studies vary in the robustness and plausibility of the finding with regard to sex, in several respects. Few have been statistically convincing, eg by demonstrating a sex-by-genotype interaction (eg Kates et al, 2006;Lang et al, 2007). Many studies simply found an association that reached significance in one sex but not in the other, without demonstrating an interaction between sex and genotype (eg Enoch et al, 2006), an approach further compromised by the fact that the nonsignificant sex often had a smaller sample size and less power than did the significant one (eg Nolan et al, 2000;Ono et al, 2004;Stein et al, 2005).…”
Section: Comt and Sexual Dimorphismsmentioning
confidence: 99%
“…Sex differences in COMT activity and in personality are well addressed in the literature (Carver and White, 1994;Cloninger et al, 2006;Darcan et al, 2008;Harrison and Tunbridge, 2008;Schmitt et al, 2008). In fact, several studies (Eley et al, 2003;Enoch et al, 2003;Reuter et al, 2006b;Lang et al, 2007) have reported sex-dependent COMT effects on personality, although others (Strobel et al, 2003;Reuter and Hennig 2005;Hoth et al, 2006;Hashimoto et al, 2007;Wacker and Gatt, 2010) reported no interactions between sex and the COMT gene.…”
Section: Introductionmentioning
confidence: 91%
“…Traits such as harm avoidance (HA) in TCI, neuroticism in NEO, and BIS all belong to negative emotionality (NEM), whereas novelty seeking (NS) in TCI, extraversion in NEO, and BAS belong to positive emotionality (PEM; Reuter et al, 2006b). Associations between COMT Val/Met and PEM/NEM were quite mixed, with nine studies showing no significant associations (Strobel et al, 2003;Tochigi et al, 2006;Ishii et al, 2007;Light et al, 2007;Urata et al, 2007;Sheldrick et al, 2008;Calati et al, 2011;Kang et al, 2010;Salo et al, 2010), seven studies showing the Val allele associated with high PEM or low NEM (Enoch et al, 2003;Tsai et al, 2004;Reuter and Hennig, 2005;Stein et al, 2005;Hoth et al, 2006;Hashimoto et al, 2007;Wacker and Gatt, 2010), and three studies showing the opposite (Met allele associated with high PEM or low NEM; Kim et al, 2006;Golimbet et al, 2007;Demetrovics et al, 2010), and three studies reported opposite pattern for males and females (Eley et al, 2003;Reuter et al, 2006b;Lang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation